2023
DOI: 10.2176/jns-nmc.2022-0212
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Subarachnoid Hemorrhage in Isolated Islands in Japan: A Population-based Study in the Miyako Islands

Abstract: The Miyako Islands (with a population of approximately 50,000) are located in southwestern Japan, with a subtropical oceanic climate. This isolated location permitted a retrospective population-based epidemiological study of subarachnoid hemorrhage. We retrospectively enrolled 110 consecutive patients from 2010 to 2019 using the subarachnoid hemorrhage database at Okinawa Miyako Hospital, which is the only local facility with neurosurgeons. We calculated the incidence of subarachnoid hemorrhage standardized to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Only studies in which incidence rates were reported by age group of 10 years, sex and country were included. The meta-analysis [2] was supplemented with a literature search from March 2017 to 1 April 2023 using the same keywords and inclusion criteria, which yielded four additional articles [8][9][10][11]. If ASAH is a multistep process the plot will be linear and will have slope of n − 1, that is, 1 less than the number of steps needed for disease onset.…”
Section: Me Thodsmentioning
confidence: 99%
“…Only studies in which incidence rates were reported by age group of 10 years, sex and country were included. The meta-analysis [2] was supplemented with a literature search from March 2017 to 1 April 2023 using the same keywords and inclusion criteria, which yielded four additional articles [8][9][10][11]. If ASAH is a multistep process the plot will be linear and will have slope of n − 1, that is, 1 less than the number of steps needed for disease onset.…”
Section: Me Thodsmentioning
confidence: 99%